2021
DOI: 10.1186/s12936-020-03573-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of mobile medical APPS (MMAS) for reading and interpreting malaria rapid diagnostic tests

Abstract: Background The World Health Organization recommends confirmatory diagnosis by microscopy or malaria rapid diagnostic test (RDT) in patients with suspected malaria. In recent years, mobile medical applications (MMAs), which can interpret RDT test results have entered the market. To evaluate the performance of commercially available MMAs, an evaluation was conducted by comparing RDT results read by MMAs to RDT results read by the human eye. Methods F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…These limitations include its low battery life, low functionality in high-dirt environments, and difficulty to use among unskilled health workers [ 21 , 22 ]. Similar results were found in a comparative evaluation of another mHealth tool used for reading and interpreting mRDTS [ 23 ]. Other POCT reader devices include handheld lateral flow immunoassays (LFIA) [ 24 , 25 ] and the mHAT RDT reader application (app) [ 26 ], although the functionality of these devices in the field is still limited and being explored [ 27 ].…”
Section: Introductionsupporting
confidence: 83%
“…These limitations include its low battery life, low functionality in high-dirt environments, and difficulty to use among unskilled health workers [ 21 , 22 ]. Similar results were found in a comparative evaluation of another mHealth tool used for reading and interpreting mRDTS [ 23 ]. Other POCT reader devices include handheld lateral flow immunoassays (LFIA) [ 24 , 25 ] and the mHAT RDT reader application (app) [ 26 ], although the functionality of these devices in the field is still limited and being explored [ 27 ].…”
Section: Introductionsupporting
confidence: 83%
“…As shown in Table S3 , the newly developed POCT showed excellent performance comparable to that of the ELISA, although the sensitivity was slightly lower. In the interpretation of POCT, visual reading can make interpretation errors, so research is focused on making accurate and improved measurements through interpretation devices [ 28 , 29 ]. When the signal intensity of neutralizing antibody was measured using an application, the T/R ratio cutoff increased in the sensitivity of the POCT.…”
Section: Discussionmentioning
confidence: 99%
“…Visual interpretation of RDTs is subjective with variable results depending on the interpreter. Analyzing RDTs with SIA has been reported to provide improved and reliable results [ 18 , 19 , 20 ]. In this study, when the signal intensity of BZ-nAb was measured using the SIA, the T/C ratio cutoff led to an increase in the sensitivity of the BZ-nAb from 92.5% to 95.0%, impacting its performance, although at the expense of its specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to visual interpretation, the signal intensity of each line (both test and control) was analyzed using a smartphone-based image analysis application (SIA). With the development of mobile medical applications for automated interpretation of RDT results, analyzing RDTs with these applications has been reported to provide improved and reliable results [ 18 , 19 , 20 ]. A pilot study of SIA evaluation using different immunochromatographic assay and results showed acceptable performance (100% sensitivity and 97.8% specificity) when compared to visual interpretation results (data not shown).…”
Section: Introductionmentioning
confidence: 99%